Multi-biofunctionalization of a titanium surface with a mixture of peptides to achieve excellent antimicrobial activity and biocompatibility. Issue 1 (13th November 2014) - Lin, Wang; Junjian, Chen; Chengzhi, Cai; Lin, Shi; Sa, Liu; Li, Ren; Yingjun, Wang
Abstract : A model for multi-biofunctionalizing a titanium surface with a mixture of peptides at desired ratios to achieve excellent antimicrobial activity and biocompatibility. Abstract : In this paper, we developed a method for covalent multi-biofunctionalization of a titanium surface with mixtures of peptides at any desired ratios using click chemistry. We demonstrated that the optimization of the types and ratios of the peptides on a titanium surface resulted in an excellent antimicrobial activity as well as good biocompatibility.